Efficacy of viscosupplementation with hyaluronic acid in temporomandibular disorders: A systematic review. Issue 11 (November 2018) - Ferreira, Natália; Masterson, Danielle; Lopes de Lima, Rodrigo; de Souza Moura, Brenda; Oliveira, Aleli T.; Kelly da Silva Fidalgo, Tatiana; Carvalho, Antônio C.P.; DosSantos, Marcos F.; Grossmann, Eduardo
Abstract: Objective: To perform a systematic review of the viscosupplementation effectiveness with hyaluronic acid (HA) in the articular Temporomandibular Dysfunctions (TMDs) clinical management. Method: Electronic searches were performed in the following databases: MEDLINE (via PubMed), Scopus, Web of Science, Cochrane Library, EMBASE, LILACS, BBO, SIGLE (System for Information on Grey Literature in Europe), ClinicalTrials.gov, and the Brazilian Clinical Trials Registry (ReBec). Only randomized clinical trials that evaluated the intra-articular administration of HA or its derivatives in osteoarthritis and/or anterior displacement of the temporomandibular joint (TMJ) disc were included. The primary outcomes evaluated were patients' self-report of pain and/or discomfort in the TMJ. Each study was assessed for the risk of bias, using the Cochrane collaboration's risk of bias tool. Results: A total of 640 studies were obtained in the electronic search. After the application of the eligibility criteria, manual search, and duplicate removal, 21 articles were included. Five articles classified their volunteers with internal derangements of the TMJ, in 4 articles the treatment was directed to participants with disc displacement with reduction and the other articles evaluated HA therapy in osteoarthritis. The protocols presented heterogeneity, varying in the form of application, associated or not with arthrocentesis, number of applications, molecular weight, dose and concentration. Nine studies presented high risk of bias. Conclusion: Due to the heterogeneity and methodological inconsistencies of the studies evaluated, it was not possible to establish the efficacy of HA in articular TMDs. Highlights: A systematic review is a key tool to establish the efficacy of clinical therapies. The synthesis of all articles evaluated revealed great heterogeneity in the clinical protocols applied. Furthermore, high risk of bias was found in several studies, limiting the level of evidence obtained. The results of the current systematic review suggest that isolated injections of HA are effective in relieving TMD pain. At the same time, arthrocentesis plus HA does not appear to be superior to arthrocentesis alone.